Availability and delivery of cardiac rehabilitation in the Eastern Mediterranean Region: How does it compare globally?. (15th June 2019) - Turk-Adawi, Karam; Supervia, Marta; Pesah, Ella; Lopez-Jimenez, Francisco; Afaneh, Jasser; El-Heneidy, Asmaa; Sadeghi, Masoumeh; Sarrafzadegan, Nizal; Alhashemi, Mohammed; Papasavvas, Theodoros; Grace, Sherry L.
Abstract: Background: This study aimed to (1) confirm cardiac rehabilitation (CR) availability, (2) establish CR density and unmet need, as well as (3) the nature of programs in the Eastern Mediterranean Region (EMR), and (4) compare these (a) by EMR country and (b) to other countries. Methods: In this cross-sectional study, a survey was administered to CR programs globally. Cardiac associations and local champions facilitated program identification. CR need was based on Global Burden of Disease study ischemic heart disease (IHD) estimates. Results: Of the 22 EMR countries, CR programs were identified in 12 (54.5%). Nine (75.0% country response rate) countries participated, and 24/49 (49.0% program response rate) surveys were initiated. There was 1 CR spot for every 104 incident IHD patients/year (versus 12 globally). One-third of responding programs were privately funded ( n  = 8; versus globally p  < .001), and in 18 (75.0%) programs patients paid some or all of the cost out-of-pocket (versus n  = 378, 36.3% globally; p  < .001). Over 80% of programs accepted guideline-indicated patients. Nurses ( n  = 20, 95.2%), cardiologists ( n  = 18, 85.7%) and dietitians ( n  = 18, 85.7%) were the most common healthcare providers on CR teams (mean = 6.4 ± 2.2/program; 5.9 ± 2.8 globally, p  = .18). On average, programs offered 8.9 ± 1.7/11 core components (versus 8.7 ± 1.9 globally, p  = .90). These were most commonly initial assessment, management of risk factors, and patient education ( n  = 21, 100.0% for each), and least commonly return-to-work counselling ( n  = 15 71.4%). Mean dose was 27.0 ± 13.5 sessions (versus 28.7 ± 27.6 globally, p  = .38). Seven (33.3%) programs offered some alternative models. Conclusion: CR is insufficiently implemented, with 2, 079, 283 more spots needed/year across the EMR. But where offered, CR is consistent with guidelines. Highlights: Cardiac rehabilitation (CR) programs were only available in 12/22 (54.5%) Eastern Mediterranean Region countries There was 1 CR spot for every 104 incident ischemic heart disease patient/year, compared to per 12 patients globally Programs were less often publicly funded than those globally, with patients paying out-of-pocket in ¾ of programs Most programs delivered all core components (but less return-to-work counselling and tobacco cessation) by a staff of 6